Effect of Storage Temperature on Sensory and Chemical Characteristics of Quail Bacem Sterile Packaging Retort Pouch - Kirmanto; Hartiningsih, Subekti; Puspasari, Diah Ayu (Journal of Food and Agricultural Product, 2025)
Quail eggs are one of the perishable materials that cause quail eggs to not be stored for a long time. One of the efforts to maintain the quality of eggs is with sterile packaging of retort pouches. This study aims to determine the effect of storage temperature (-14°C, 5°C, and 25°C) on sensory characteristics (Aroma, Taste, Color, Texture, and Overall) and Chemical characteristics (Fat) of the best retort pouch sterile packaged quail egg processed products from the sensory characteristics test stored for 30 days. This study used a non-factorial Complete Random Design (RAL) with 30 panelists and 2 repetitions of analysis on chemical characteristics testing. The data from the study was calculated using Oneway ANOVA with a level of 5% (0.05) and if there was a difference. Followed by Duncan's Multiple Rnage Test (DMRT) using SPSS 26. Based on the results of the study, it is known that storage temperature has a real effect on sensory characteristics, storage temperature of 5°C is preferred compared to temperature of 25°C and -14°C with fat content at storage temperature of -14°C which is 15.51%, temperature of 5°C which is 16.85%, and temperature of 25°C which is 15.13% Keywords: Quail Eggs, Temperature, Sensory, Chemical